Biomimetic crystallization of calcium carbonate in the presence of water-soluble zwitterionic block copolymer - Yazici, Ozlem; Karaman, Ferdane (WILEY, 2019)
Crystallization of calcium carbonate (CC) in aqueous solutions by gas-liquid diffusion procedure was investigated systematically in the presence of poly(4-sulfonic acid diphenylamine)-block-poly(ethylene glycol) (PSDA-b-PEG), wherein the PSDA block is a polymeric zwitterion. PSDA-b-PEG was synthesized with the reaction of tosylated PEG and amine-functionalized PSDA and was characterized by nuclear magnetic resonance. The parameters such as, block copolymer concentration, crystallization time and initial pH were considered as indicators of block copolymer's capability in controlling the morphology of CC particles(.) The particles were characterized by Fourier transform infrared, scanning electron microscopy, and X-ray diffraction. The results suggest that PSDA-b-PEG is a suitable template to control the growth mechanism of CC to produce meso-sized particles with different morphologies. POLYM. ENG. SCI., 59:96-102, 2019. (c) 2018 Society of Plastics Engineers
Keywords: DENSITY POLYETHYLENE; CRYSTAL PHASE; AMINO-ACIDS; CACO3; POLYPROPYLENE; MORPHOGENESIS; MESOCRYSTALS; MORPHOLOGIES; AGGREGATION; POLYMORPHS; Engineering; Polymer Science